Fecal Transplantation Successfully Treats Recurrent D-Lactic Acidosis in a Child With Short Bowel Syndrome. (July 2017) - Davidovics, Zev H.; Vance, Katherine; Etienne, Nancy; Hyams, Jeffrey S.
D-lactic acidosis can occur in patients with short bowel syndrome (SBS) when excessive malabsorbed carbohydrate (CHO) enters the colon and is metabolized by colonic bacteria to D-lactate. D-lactate can be absorbed systemically, and increased serum levels are associated with central nervous system toxicity manifested by confusion, ataxia, and slurred speech. Current therapy, usually directed toward suppressing intestinal bacterial overgrowth and limiting ingested CHO, is not always successful. Fecal transplantation, the infusion of donor feces into a recipient's intestinal tract, has been used for decades to treat recurrent Clostridium difficile infection, and case reports document its use in the successful treatment of constipation, diarrhea, and abdominal pain. The exact mechanism of action is unknown, but it is surmised that the alteration of the intestinal microbiome, as well as the reintroduction of potential beneficial microbes, helps mediate disease. Here we present the case of a child with SBS and recurrent, debilitating D-lactic acidosis, which was successfully treated with fecal transplantation.